Distribution of some amphibians from central western Mexico: Jalisco State - Veronica Carolina Rosas Espinoza; Jesus Mauricio Rodriguez Canseco; Ana Luisa Santiago Pérez; Alberto Ayón Escobedo; Matías Domínguez Laso (Revista Mexicana de Biodiversidad)
The amphibian fauna from central western Mexico has not been studied enough. Particularly for the state of Jalisco, Flores-Villela and Pérez-Mendoza (2006) reported five publications regarding  herpetofauna checklists done between 1958 to 1994 and the majority of these works were realized on seasonally tropical dry forest at the Pacific coast (Casas Andreu 1982; García y Ceballos 1994; Ramírez-Bautista 1994). Since 1995, other studies have been made, like the one done by Peterson et al. (1995) about a range extension for Eleutherodactylus occidentalis and Hyla eximia on Chapala Lake; another study done by Ponce-Campos et al. (2003) on the subtropical dry forest at the Barranca of Rio Santiago where they registered a range extension of Eleutherodactylus pallidus. During 2004, Ponce-Campos and Ortega-Huerta reported the herpetofauna from Guadalajara city and its surroundings. Loeza-Corichi conducted a study on the species richness of amphibians and reptiles in an altitudinal gradient in Cerro Grande, Sierra de Manantlán Biosphere Reserve. On 2006, Riojas-López and Mellink registered the herpetofauna on shrubland and cultivated stands at the Mexican Plateau. Recently, Reyna et al. (2007) and Orozco-Uribe (2009) reported the herpetofauna checklist for two natural protected areas:  La Primavera and Las Joyas Research Station at Sierra de Manantlán, respectively. On La Primavera the dominant vegetation types are temperate forest (pine-oak) and tropical deciduous forest; on Sierra de Manantlán are temperate forest (pine-oak) and cloud forest. Sierra de Quila is a natural protected area located on central Jalisco (20.1429–20.2137°N, 103.5649 – 104.0753°W). During 15 months, from January 2009 to september 2010 we surveyed amphibians on the altitudinal gradient including all vegetation types: cloud forest, pine-oak forest, oak forest, riparian forest and tropical deciduous forest. We registered 11 noteworthy range extensions for amphibians within Jalisco State and into Sierra de Quila. We collected two adults of Incilius marmoreus, eight adults of Craugastor occidentalis, one adult of Plectrohyla bistincta, one adult of Smilisca baudinii, two Lithobates neovolcanicus and three neotenic and one adult of Ambystoma flavipiperatum in Sierra de Quila. All these specimens are in herpetological collection of the zoological museum Alfonso L. Herrera, Facultad de Ciencias, Universidad Nacional Autónoma de Mexico (MZFC). Aditionally we took pictures of one adult of Craugastor hobartsmithi, one adult of Craugastor pygmaeus, one adult of Eleutherodactylus angustidigitorum and one adult of Lithobates forreri and these were deposited in the UTA digital collection.